Synthesis, Characterization and Biological Activity of some new phthalimides and maleimides derivetives containing benzothiazole ring - A. Mahmoud, Muhanned; Qusay Kadhim, Atyaf; Younus Abed*, Ahmed (Al-Qadisiyah Journal of Pure Science, 2018)
In this work, a series of new3-nitro phthalimides and bromo maleimides derivetives containing benzothiazole ring were synthesized, the Synthesis of series of N-(substituted benzothiazole-2-yl) 3-nitro phthalimide were performed via three steps, the first one involved preparation of a series of substituted 2-aminobenzothiazole via reaction of different primary aromatic amines with ammonium thiocyanate and bromine in glacial acetic acid, In the second step the prepared amino benzothiozoles were introduced in reaction with 3- nitro phthalic anhydride producing a series of N-(substituted benzothiazole-2-yl) 3- nitro phthalamic acid, while Fusion Method used in preparation of a series N-(substituted benzothiazol-2-yl) bromo maleimide via Fusion The prepared substituted 2-aminobenzothiazole with Bromo Maleic anhydride to producing a series of N-(substituted benzothiazol-2-yl) bromo maleimide ,the synthesized compounds were identified depending upon physical and spectral method, Microbiological activities of the prepared compounds against four types of bacteria and one type of fungi were evaluated and the results showed that the most tested compounds have good antibacterial and anti fungi activity .